Pillarization of Sumatera Bentonite by Sodium-assisted As Effective Adsorbent of Anionic Surfactants Sodium Lauryl Sulphate (SLS) Waste - Yusuf Mathiinul Hakim; Rahma Dinta Astuti; Idha Royani; Mardiyanto Mardiyanto; Risfidian Mohadi (Bulletin of Chemical Reaction Engineering & Catalysis, 2023)
In this work, the Sumatera bentonite was sodium-pillarized in a new low-temperature and restricted time preparation route and then applied in anionic surfactant sodium lauryl sulphate removal. Structure characterization used Fourier Transform Infra Red (FT-IR), Scanning Electron Microscope - Energy Dispersive X-ray (SEM-EDX), X-ray Diffraction (XRD), and Brunauer–Emmett–Teller (BET) analysis. A strong peak at 22° and 35.66° in XRD analysis was detected as Sodium-pillar that increased crystallinity, then the functional changes of dehydration in lattice structure were detected in 1013 cm−1 by FTIR analysis. The morphology and compositional transformation were analyzed by SEM-EDX and BET analysis, denoted by increasing particle shape and sodium intercalant composition homogeneity. Moreover, the surface area increased from 61.791 to 66.086 m2/g. The sodium lauryl sulphate adsorption by bentonite-Na reached maximum capacity at 8.403 mg/g, which is higher than the pristine bentonite (5.747 mg/g) under the optimum condition. The adsorption mechanism is feasible, endothermic, and conformed to the pseudo-second-order and Freundlich adsorption model. The new route proposed for sodium intercalation effectively improves the Sumatera bentonite adsorption ability to remove sodium lauryl sulphate waste. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).